Clinical case report of a professional triathlete with positive exercise stress test but negative coronary angiography - Assisi, E.; Libener, E.; Grossgasteiger, S.; Mur, C.; Resnyak, S. (The Journal of Sports Medicine and Physical Fitness, 2023)
This article describes the clinical case of a master athlete, practising triathlon, who came to our Sports Medicine Center to be eligible for competitive sport. The subject, who had a family history of ischemic heart disease, presented a significant lowering of the ST segment in the inferolateral leads on the maximal cycle ergometer exercise test. Inducible myocardial ischemia emerged from the second level investigations. However, it was not confirmed by two coronary angiographies, the second performed after 9 years. The subject remained asymptomatic for the entire duration of the follow-up and in excellent clinical conditions, having never shown adverse events of cardiovascular nature.